Assessment of nutritional quality of cheeses and cheese analogues on the market of the Republic of Serbia - Đurović Ana D.; Kravić Snežana Ž.; Stojanović Zorica S.; Iličić Mirela D.; Kanurić Katarina G.; Vukić Dajana V.; Vukić Vladimir R.; Degenek Jovana Đ.; Ćurić Katarina S. (Acta Periodica Technologica, 2022)
In this paper, the nutritional quality of cheese samples and cheese analogues was assessed throughout the fatty acid profile and lipid indices. The research included cheese analogues in which milk fat was completely replaced by vegetable fat with the addition of palm and coconut oil, as well as mixed cheese analogues products, whose production was based on the use of palm oil, milk protein and cheese. Fatty acid profile was analysed by gas chromatography-mass spectrometry (GC-MS), while the atherogenic index, thrombogenic index and hypocholesterolemic/hypercholesterolemic ratio were calculated for the estimation of the lipid quality of the analysed samples. GC-MS analysis revealed the presence of 29 fatty acids in the analysed samples, among which dominated palmitic, stearic, oleic and linoleic fatty acid. Samples of cheese analogues showed improved fatty acid composition with a decreased content of saturated fatty acids and increased content of unsaturated fatty acids (monounsaturated and ω6 fatty acids). Values of atherogenic, thrombogenic indices and hypocholesterolemic/ hypercholesterolemic ratio (AI, TI and H/H) in the analysed samples varied in the range 0.81-11.89, 1.64-5.22 and 0.14-1.31, respectively. Lower AI and TI values accompanied by higher H/H values were observed for cheese analogues obtained by partial or complete substitution of milk fat with palm oil. Cheese analogue, in which production coconut oil completely replaced milk fat, demonstrated unfavourable fatty acid content and accompanying lipid indices, indicating the low nutritional quality of the specific sample.